2021
DOI: 10.3390/cancers13020292
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Testing and Squamous Cell Carcinoma of the Head and Neck: A Multicenter Study on the Diagnostic Reproducibility of Different Protocols

Abstract: Immune checkpoint inhibitors for blocking the programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) axis are now available for squamous cell carcinoma of the head and neck (HNSCC) in relapsing and/or metastatic settings. In this work, we compared the resulting combined positive score (CPS) of PD-L1 using alternative methods adopted in routine clinical practice and determined the level of diagnostic agreement and inter-observer reliability in this setting. The study applied 5 different protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 23 publications
(18 reference statements)
4
48
0
Order By: Relevance
“…This was also reflected in the concordance for the CPS cutoffs, which was notably better for human-machine (κ = 0.58) than that for human-human (κ = 0.43). Our kappa values were in the range to a multicenter inter-rater study for HNSCC, which reported a Fleiss' kappa value between 0.303 and 0.557 for the CPS [51]. Overall, this supports the potential clinical value of machine-based decision finding for the treatment of HNSCC based on a CPS cutoff of ≥1.…”
Section: Discussionsupporting
confidence: 75%
“…This was also reflected in the concordance for the CPS cutoffs, which was notably better for human-machine (κ = 0.58) than that for human-human (κ = 0.43). Our kappa values were in the range to a multicenter inter-rater study for HNSCC, which reported a Fleiss' kappa value between 0.303 and 0.557 for the CPS [51]. Overall, this supports the potential clinical value of machine-based decision finding for the treatment of HNSCC based on a CPS cutoff of ≥1.…”
Section: Discussionsupporting
confidence: 75%
“…Although our study was conducted on tissue-microarray (TMA) and not on whole tissue sections, our results are in line with the previous observations. One previous study [ 22 ], reporting low concordance between the two Dako platforms was performed using 22C3 antibody as LTD on Dako Omnis before the PharmDX kit had been optimized for use on this platform. We providednewevidence that validates the PharmDX assay optimized for use on Dako Omnis platform in comparison to Dako Autostainer link48, in the light of the ongoing shift between the two platforms.…”
Section: Discussionmentioning
confidence: 99%
“…compared the reference 22C3 assay with a 22C3 laboratory developed test (LDT) and the SP263 assay in 143 cases. A smaller series published by Crosta et al 21 tested the performance of five different PD‐L1 protocols with clones SP142, SP263, and 22C3 on various platforms against the 22C3 pharmDx on 15 cases/30 cores. The aforementioned studies utilized a tissue microarray (TMA) and were comprised of cases from several sites in the head and neck region, with PD‐L1 assessed centrally by trained pathologists.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, training in this regard has been shown to be important 35 . However, when pathologists are trained, the reproducibility among them appears to be high in assessing CPS, with ICC≥0.70 21,29 or excellent ≥0.90 20 with all of the assays including 22C3 pharmDx, SP263, and SP142. Some studies suggest better concordance for pathologists with the SP263 assay when assessing both CPS or separately counting tumor and immune cells, with an almost perfect kappa of 0.836 and in the range of moderate to substantial for the clones SP142, 22C3, and E1L3N 24 .…”
Section: Resultsmentioning
confidence: 99%